Analysis of fingerprint minutiae to form fingerprint identifier - Ziad Alqadi; Mohammad Abuzalata; Yousf Eltous; Ghazi M. Qaryouti (Society of Visual Informatics, 2020)
Detailed human fingerprints, almost unique, are difficult to change and are permanent on an individual's life, making them suitable as long-term signs of human identity. They may be employed by the police or other authorities to identify individuals who wish to conceal their identity, or identify incapacitated or deceased persons and therefore cannot identify them, as in the aftermath of a natural disaster. Fingerprints images are very important data type due to wide applications requiring this type, so extraction a fingerprint identifier is a vital issue. In this paper we will analyse the fingerprints images in order to extract minutiae from the images, these minutiae will be used to construct the fingerprint identifier, the proposed procedure will be implemented and tested to ensure that the procedure generates a simple and unique identifier, which can be easily used to recognize the fingerprint in any recognition system.